2015
DOI: 10.1159/000381314
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Attenuates Adriamycin-Induced Focal Segmental Glomerulosclerosis

Abstract: Background/Aim: Focal segmental glomerulosclerosis (FSGS) is a specific pattern of chronic renal injury with progressive glomerular scarring. The phenotypic alterations that contribute to FSGS include inflammatory response and oxidative stress. Astaxanthin (ATX) has a broad range of biological functions, particularly antioxidant and anti-inflammatory ones. This study was designed to evaluate the renoprotective effect of ATX treatment on Adriamycin-induced FSGS. Methods: In Balb/c mice, Adriamycin nephropathy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The gene expression in each sample was analyzed in duplicate and normalized against the internal control gene ­GAPDH. Relative quantification of the target gene expression in patients compared with normal samples was performed with the ΔΔCt method [15]. …”
Section: Methodsmentioning
confidence: 99%
“…The gene expression in each sample was analyzed in duplicate and normalized against the internal control gene ­GAPDH. Relative quantification of the target gene expression in patients compared with normal samples was performed with the ΔΔCt method [15]. …”
Section: Methodsmentioning
confidence: 99%
“…The gene expression in each sample was analyzed in duplicate and normalized against the internal control gene GAPDH. Relative quantification of the target gene expression in patients compared with normal samples was performed using the ΔΔCt method [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in this study, we also build FSGS animal models by injecting adriamycin in the tail vein of Balb/c mice. Thus, we focus on the renoprotective role of RSV in FSGS using adriamycin nephropathy (AN) mouse models [19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…effect 34,35 . Studies have shown that the protective effects of astaxanthin against many kidney diseases is related to antiapoptosis 3,4,36 . Considering the crucial role of oxidative stress in inducing pathological changes of IR and the antioxidant properties of ATX, ATX might alleviate tubular necrosis/ apoptosis and inflammation via scavenging free radical 19 .…”
Section: Anti-apoptosis Effectsmentioning
confidence: 99%